2022
DOI: 10.1021/acsnano.1c09864
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Fingerprints on Bowl-Shaped Submicroreactor Chip for Chemotherapy Monitoring

Abstract: Chemotherapy is a primary cancer treatment strategy, the monitoring of which is critical to enhancing the survival rate and quality of life of cancer patients. However, current chemotherapy monitoring mainly relies on imaging tools with inefficient sensitivity and radiation invasiveness. Herein, we develop the bowl-shaped submicroreactor chip of Au-loaded 3-aminophenol formaldehyde resin (denoted as APF-bowl&Au) with a specifically designed structure and Au loading content. The obtained APF-bowl&Au, used as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…Moreover, the reducing capacity of the hydroxymethyl groups is not sufficient to reduce Pd 2+ to form PdNPs (Figure S17, Supporting Information). [ 50,51 ] Therefore, our developed method is very effective for spatial location controllable synthesis of AuNPs and PdNPs, selectively. We also investigated the inductively coupled palsma optical emission spectroscopy (ICP‐OES) (Table S2, Supporting Information) and X‐ray diffraction (XRD) (Figure S18, Supporting Information) for those bimetallic nanomaterials, whose detailed analyses are shown in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the reducing capacity of the hydroxymethyl groups is not sufficient to reduce Pd 2+ to form PdNPs (Figure S17, Supporting Information). [ 50,51 ] Therefore, our developed method is very effective for spatial location controllable synthesis of AuNPs and PdNPs, selectively. We also investigated the inductively coupled palsma optical emission spectroscopy (ICP‐OES) (Table S2, Supporting Information) and X‐ray diffraction (XRD) (Figure S18, Supporting Information) for those bimetallic nanomaterials, whose detailed analyses are shown in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, matrices are considered the most fundamental parameters in metabolic analysis, in which inorganic materials with stable structures and UV-absorbing are preferred organic compounds with strong background interference (Noh et al, 2017;Kim et al, 2021). Existing matrices are mostly based on plasmonic metal (Du et al, 2019;Wang et al, 2021;Yin et al, 2022), metal oxides (Kim et al, 2020), carbon (Coffinier et al, 2012), and silicon (Gao et al, 2016;Korte et al, 2016). Typically, metals (e.g., Au) with pre-selected structures display surface plasmon resonance and generate hot carriers under laser irradiation, serving as an emerging class of matrix materials in chip design (Sun et al, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The development and occurrence of diseases, especially cancer, consist of complicated biological mechanisms, in which single modal data is insufficient for analyzing the pathogenic factors. Multi‐omics analyses will not only be able to reveal the complex mechanisms underlying cancer progression and development, [ 14 ] but also have been proposed as the key to promoting precision medicine in the clinic, such as diagnostic/therapeutic biomarker discovery, [ 15 ] treatment response evaluation, [ 16 ] and survival prediction. [ 17 ] Particularly, a recent prospective and interventional study demonstrated that blood tests with positron emission tomography‐computed tomography can localize several types of cancers safely and precisely for individuals who were not previously known to have cancer, [ 18 ] proofing the clinical potential of integrating biological biomarkers with radiological features for early cancer screening.…”
Section: Introductionmentioning
confidence: 99%